Applying systems thinking to improve the safety of work-related drivers: A systematic review of the literature. (December 2022) - Newnam, Sharon; St Louis, Renee; Stephens, Amanda; Sheppard, Dianne
Highlights: A gap in prevention is the ability to learn light vehicle work-related driving crashes. A systematic review was undertaken to identify factors associated safety outcomes. A systems thinking framework was used to illustrate current understanding. This study presents the first step in developing system thinking prevention tools. Abstract: Introduction: Light vehicles (<4.5 tons) driven for work purposes represent a significant proportion of the registered motor vehicles on our roads. Drivers of these vehicles have significant exposure to the dangers of the road transport environment. To optimize safety for these workers, it is critical to understand the factors contributing to risk of being involved in an incident. This information can then be used to inform the review and revision of existing risk controls and the development of targeted prevention activities. Method: The aim of the study was to undertake a systematic review of the literature to identify the factors associated with work-related driving incidents. The factors identified in the review were represented within an adapted version of Rasmussen's risk management framework (Rasmussen, 1997 ). Fifty studies were analyzed following data screening and review of full text. The highest proportion of risk factors were categorized at the lower levels of the system, including the 'Drivers and Other Road Users' level (n = 20, 44.4%) and the 'Equipment, Environment, and Meteorological Surroundings' level (n = 19, 42.2%). There were no risk factors identified at the 'Regulatory and Government Bodies' levels of the framework, confirming the narrow investigative scope of past research and the need to acknowledge a broader range of factors within and across higher levels of the system. Conclusions: The findings of this study inform the direction of future research and design of targeted prevention activities capable of creating system change for the safety of work-related drivers.